The Current Report of Herpetofauna in Enggano Island, Bengkulu, Indonesia, with Two New Record of Amphibian Species - Vestidhia Yunisya Atmaja; Apriza Hongko Putra; Eti Widiya Lestari; Riansi Silaban (Universitas Labuhanbatu, 2024)
Enggano Island has a unique and interesting endemic species to study. Data collection on the Enggano's herpetofauna was last carried out in 2015, and there was a data gap for six years. Therefore, it is necessary to research herpetofauna diversity on the island. The study used Visual Encountered Survei (VES) combined with patch and time search sampling at diurnal and nocturnal active times. We also compiled the data on herpetofauna species in books, journal publications, database specimens from museums worldwide, and recorded observations of individual species. We surveyed four research sites on Enggano Island (Kaana, Malakoni-Apoho, Meok, and Banjarsari). We preserved some specimens for each unprotected species in ethanol 70% and identified with Sumatran herpetofauna field guide. From the research, we concluded that there are 15 species of herpetofauna found in this study (4 species of amphibians and 11 species of reptiles). We found 2 endemic species of the island (Draco modiglianii and Cnemaspis modiglianii). Previous research has not reported two new record species of amphibians, i.e., Fejervarya limnocharis and Duttaphrynus melanostictus. This research has not yet represented herpetofauna's true diversity on Enggano Island. The number of these species can still increase along with expanding the research study area, especially in conservation areas managed by BKSDA. Continuous exploration and monitoring need to be carried out to ensure future conservation management